Efficiency of RCC piles with helical grooves subjected to axial and lateral loads in cohesionless soil - Arun Kumar Y. M.; Kiran K. Shetty; A. Krishnamoorthy (Cogent Engineering, 2024)
AbstractThis paper presents an experimental and numerical investigation of RCC (Reinforced Concrete) piles with helical grooves under axial and lateral loads in cohesionless soil. A set of experiments is carried out to assess the performance of RCC piles with helical grooves. To replicate the experimental findings, the Finite Element Method (FEM) is employed using Abaqus software. Three-dimensional (3D) models are created to represent both the pile and the soil using Abaqus. The paper compares settlement characteristics and lateral displacement of plain RCC piles and RCC piles with helical grooves. This study also evaluates the impact of varying the pitch of helical grooves on enhancing pile performance. The results indicate that RCC piles with helical grooves outperform plain RCC piles in terms of both axial and lateral load-carrying capacity, inferred from both experimental and analytical techniques.